Traceability Automation in Coffee Production: A Case Study on QR Code Integration to Optimize Manual Steps - Eduarda Terra Querme, Mayara; Araújo Lima, Danielli (Archives of Advanced Engineering Science, 2023)
Agriculture and coffee production are vital to Brazil’s economy, generating jobs, driving regional development, and contributing significantly to the trade balance, making Brazil a leading coffee producer and exporter. In this context, this scientific article proposes automating coffee production traceability using QR-Codes to optimize processes, enhance quality, safety, and sustainability in the supply chain under the Industry 4.0 paradigm. We employ BPMN modeling to delineate coffee production stages, leveraging QR-Codes for data collection and registration during activities like harvesting, washing, drying, processing, storage, and farm certification validation. QR-Codes streamline operations, reduce errors, and enhance traceability, involving actors ranging from harvesters to quality personnel, inspectors, and clerks. The study scrutinizes coffee transfer from rural producers to warehouses, optimizing stock and delivery management. The main results obtained were the significant reduction in the number of employees, the reduction of activities and consequently the time, finally, the assertiveness to complete the process. Received: 29 July 2023 | Revised: 16 October 2023 | Accepted: 28 October 2023 Conflicts of Interest The authors declare that they have no conflicts of interest to this work. Data Availability Statement Data sharing is not applicable to this article as no new data were created or analyzed in this study.